Effects of cadmium exposure on intestinal microflora of Cipangopaludina cathayensis - Jiang, Jiao-yun; Li, Wen-hong; Wu, Yang-yang; Cheng, Chun-xing; Ye, Quan-qing; Feng, Jia-xun; Xie, Zhi-xun (Frontiers in Microbiology, 2022)
As one of the most environmentally toxic heavy metals, cadmium (Cd) has attracted the attention of researchers globally. In particular, Guangxi, a province in southwestern China, has been subjected to severe Cd pollution due to geogenic processes and anthropogenic activities. Cd can be accumulated in aquatic animals and transferred to the human body through the food chain, with potential health risks. The aim of the present study was to explore the effects of waterborne Cd exposure (0.5 mg/L and 1.5 mg/L) on the intestinal microbiota of mudsnail, Cipangopaludina cathayensis, which is favored by farmers and consumers in Guangxi. Gut bacterial community composition was investigated using high-throughput sequencing of the V3–V4 segment of the bacterial 16S rRNA gene. Our results indicated that C. cathayensis could tolerate low Cd (0.5 mg/L) stress, while Cd exposure at high doses (1.5 mg/L) exerted considerable effects on microbiota composition. At the phylum level, Proteobacteria, Bacteroidetes, and Firmicutes were the dominant phyla in the mudsnail gut microbiota. The relative abundances of Bacteroidetes increased significantly under high Cd exposure (H14) (p < 0.01), with no significant change in the low Cd exposure (L14) treatment. The dominant genera with significant differences in relative abundance were Pseudomonas, Cloacibacterium, Acinetobacter, Dechloromonas, and Rhodobacter. In addition, Cd exposure could significantly alter the pathways associated with metabolism, cellular processes, environmental information processing, genetic information processing, human diseases, and organismal systems. Notably, compared to the L14 treatment, some disease-related pathways were enriched, while some xenobiotic and organic compound biodegradation and metabolism pathways were significantly inhibited in the H14 group. Overall, Cd exposure profoundly influenced community structure and function of gut microbiota, which may in turn influence C. cathayensis gut homeostasis and health.